An Assessment of HIV‐Infected Patients Dying in Care for Deceased Organ Donation in a United States Urban Center. Issue 8 (14th May 2015) - Richterman, A.; Sawinski, D.; Reese, P. P.; Lee, D. H.; Clauss, H.; Hasz, R. D.; Thomasson, A.; Goldberg, D. S.; Abt, P. L.; Forde, K. A.; Bloom, R. D.; Doll, S. L.; et al.
<x xml:space="preserve">Abstract</x> Organ transplantation is an acceptable option for human immunodeficiency virus (HIV)‐infected patients with end‐stage kidney or liver disease. With worse outcomes on the waitlist, HIV‐infected patients may actually be disproportionately affected by the organ shortage in the United States. One potential solution is the use of HIV‐infected deceased donors (HIVDD), recently legalized by the HIV Organ Policy Equity (HOPE) Act. This is the first analysis of patient‐specific data from potential HIVDD, retrospectively examining charts of HIV‐infected patients dying in care at six HIV clinics in Philadelphia, Pennsylvania from January 1, 2009 to June 30, 2014. Our data suggest that there are four to five potential HIVDD dying in Philadelphia annually who might yield two to three kidneys and three to five livers for transplant. Extrapolated nationally, this would approximate 356 potential HIVDD yielding 192 kidneys and 247 livers annually. However, several donor risk indices raise concerns about the quality of kidneys that could be recovered from HIVDD as a result of older donor age and comorbidities. On the other hand, livers from these potential HIVDD are of similar quality to HIV‐negative donors dying locally, although there is a high prevalence of positive hepatitis C antibody.